Atorvastatin Attenuates Remnant Lipoprotein-Induced Monocyte Adhesion to Vascular Endothelium Under Flow Conditions - Kawakami, Akio; Tanaka, Akira; Nakajima, Katsuyuki; Shimokado, Kentaro; Yoshida, Masayuki (Circulation research, 2002)
ABSTRACT—Remnant lipoproteins have been reported to play a causative role in atherogenesis. We investigated the effect of remnant-like lipoprotein particles (RLPs) on monocyte-endothelial interaction and their potential regulation by atorvastatin. Monocytic U937 cells were incubated with RLPs isolated from hypertriglyceridemia subjects and their adhesion to human umbilical vein endothelial cells (HUVECs) was examined under flow conditions. Incubation of U937 cells with 15 μg protein/mL RLPs increased their adhesion to HUVECs activated with IL-1β (untreated6.8±1.6 cells/HPF versus RLPs16.2±3.3 cells/HPF, P <0.05). Flow cytometric analysis revealed that incubation with RLPs increased expression levels of CD11a, CD18, and CD49d in U937 cells. Moreover, RLP-induced RhoA activation as well as FAK activation was seen in U937 cells, and RLP-induced RhoA activation seemed to be involved with PKC-dependent signaling. To explore the effect of atorvastatin on RLP-induced U937 cell adhesion to HUVECs, U937 cells were incubated with RLPs in the presence of atorvastatin. Pretreatment of U937 cells with 10 μmol/L atorvastatin significantly decreased RLP-induced U937 cell adhesion to activated HUVECs (RLP 15.2±1.5 cells/HPF versus atorvastatin+RLP 10.2±1.0 cells/HPF;P <0.05) and decreased the enhanced integrin expression in RLP-treated U937 cells. Atorvastatin also inhibited RLP-induced RhoA activation and FAK activation in U937 cells. In summary, RLPs induced monocyte adhesion to vascular endothelium by sequential activation of PKC, RhoA, FAK, and integrins, indicating a role of remnant lipoproteins in vascular inflammation during atherogenesis. Atorvastatin attenuated this enhanced monocyte adhesion to HUVECs, suggesting an antiinflammatory role for this compound.